Pengaruh Pemberian Latihan Stepping Strategy Terhadap Keseimbangan Dinamis pada Lanjut Usia - Vamula, Alfinta Septa; , Totok Budi Santoso, S.Fis., S.Pd., M.P.H (2016)
Background: On the elderly will occur decrease physiological of musculoskeletal system, especially the effect on the balance controller. When walking, the elderly will increase fulcrum of the position changes with a wider foundation, and the brief rivet phase. Giving training such stepping strategy exercise can increase the dynamic control of the dynamic balance of elderly. Objective: To determine the effect of stepping strategy exercise to dynamic balance on elderly. Benefits: To identify the effect of stepping strategy exercise to dynamic balance on elderly. Method: Type of research is quasi experiment with two groups pre-test and post-test design, which is sampled at a given treatment group stepping strategy exercise for 6 weeks with a frequency of exercise 2 times a week. Measurement of dynamic balance using the Timed Up and Go Test. Data were analyzed using the Wilcoxon Test to test influence and Mann-Whitney Test to test different between groups and test different influences. Results: There was no difference between the value of pre-test treatment and control groups after the Mann-Whitney Test p-value 0.151. There is a difference between the value of post test treatment and control group to increase the dynamic balance after the Mann-Whitney Test p-value 0.013. There is an effect stepping strategy exercises to increase the dynamic balance on elderly after the Wilcoxon test p-value 0,010 (treatment group) and p-value 0.021 (control group). There is a difference between the effect of the treatment group and the control to increase the dynamic balance on elderly after the Mann-Whitney Test p-value 0.005. Conclusion: There is an effect stepping strategy exercise to dynamic balance on elderly. Keywords: Dynamic Balance, Elderly